Allele loss in colorectal cancer at the Cowden disease/juvenile polyposis locus on 10q. - Frayling, I; Bodmer, W; Tomlinson, I (1997)
The genes that are mutated in inherited cancer syndromes are often involved in the pathogenesis of sporadic cancers of the types that characterize those syndromes. In colorectal cancer such loci include the familial adenomatous polyposis (APC) gene and the hereditary nonpolyposis colorectal cancer (DNA mismatch repair) genes. Juvenile hamartomatous polyposis syndromes, which include Juvenile Polyposis and Cowden disease, also predispose to colorectal cancer. The gene for Cowden disease has recently been localized to chromosome 10q22-q23, and a juvenile polyposis locus, JP1, has been reported as mapping to the same location. We have studied up to 70 cases of sporadic colorectal cancer for allele loss at markers predominantly on the long arm of chromosome 10, including loci flanking the putative Cowden Disease/JP1 locus. Frequencies of allele loss of about 35% were found close to this locus, whereas low frequencies of allele loss were found elsewhere on 10q. Mutations at the putative Cowden Disease/JP1 locus may therefore be important in sporadic colorectal cancer and fine mapping of allele loss on 10q in sporadic colon cancers may help to refine the position of this gene.